[OP.3C.02] EXERCISE SYSTOLIC BLOOD PRESSURE AT MODERATE WORKLOAD: WHICH THRESHOLD LEVEL PREDICTS CORONARY HEART DISEASE IN HEALTHY, MIDDLE-AGED MEN?. (September 2017) - Mariampillai, J.; Engeseth, K.; Kjeldsen, S.; Prestgaard, E.; Gjesdal, K.; Liestøl, K.; Erikssen, J.; Bodegard, J.; Grundvold, I.; Skretteberg, P.
Abstract : Objective: Elevated exercise systolic blood pressure (SBP) is associated with increased risk of coronary heart disease (CHD). However, at which threshold level of exercise SBP the risk of CHD is elevated, has not been established. We aimed to investigate this by performing analyses for threshold levels between 160 mmHg and 195 mmHg. Design and method: In the Oslo Ischemia Study, 1999 healthy, middle-aged men were able to complete a six-minute, ECG-monitored bicycle test at 100W workload (Survey 1). At Survey 2, seven years later, 1392 men were still healthy and included in this study. The men were successively grouped by SBP at 100W (SBP100W) below or above incremental threshold levels measured at both surveys. Group 1 had SBP100W < threshold level at both Survey 1 and 2, Group 2 had SBP100W >/= threshold level at Survey 1 or Survey 2, and Group 3 had SBP100W >/= threshold level at both Survey 1 and Survey 2. Stepwise risk analyses were performed for incremental thresholds raised by 5 mmHg in each step, from 160 mmHg to 195 mmHg. Outcome was CHD, defined as first event of fatal/non-fatal myocardial infarction or angina pectoris, and participants were followed for 28 years. Hazard ratios were calculated using Cox proportional hazards model adjusted for age, SBP at rest, smoking status, total serum cholesterol, family history of CHD and physical fitness, and Group 3 was compared with Group 1 for each 5 mmHg increment in threshold level of SBP100W. Results: When comparing Group 3 with Group 1, there was significantly increased risk of CHD in Group 3 at all threshold levels of SBP100W from 165 mmHg to 190 mmHg (figure). With increasing average SBP100W in Group 1 as the threshold level increases, the stable hazard ratios represent increasing risk of CHD with increasing SBP100W. Figure. No caption available. Conclusions: There is an increased long-term risk of coronary heart disease in men showing sustained exercise systolic blood pressure >/ = 165 mmHg. The association is independent of classical cardiovascular risk factors, systolic blood pressure at rest and physical fitness.